2005
DOI: 10.1532/ijh97.05034
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hepatic Injury Caused by Imatinib Mesylate Administered for the Treatment of Chronic Myeloid Leukemia and the Efficacy of Prednisolone for its Management

Abstract: Imatinib mesylate is a specific inhibitor of BCR-ABL tyrosine kinase, which is now widely used for the treatment of chronic myeloid leukemia (CML) with a high efficacy. Although severe hepatic injury caused by imatinib mesylate is rare, such a side effect may force patients to discontinue taking imatinib mesylate. In the present paper, we report on the case of a 51-year-old woman with CML who experienced hepatic injury with severe hyperbilirubinemia caused by imatinib mesylate. The findings from a liver biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Additionally, in the context of a clear danger signal, such as underlying inflammation, infection or trauma, all of which may constitute the danger signal, the risk of IDRs increases [52]. The usefulness of corticosteroids may be based on their ability to suppress the inflammatory response in the liver as a part of drug hypersensitivity or an immuno-allergic reaction, and this supports the speculation that an allergic mechanism may be involved in the TKIassociated liver injury seen in these patients [48,49]. Therefore, cautiously re-challenging after complete resolution of the liver injury under steroid administration and with very gradual dose increment may allow patients who have developed severe liver toxicity to continue taking the drug [51].…”
Section: Reversibility Of Toxicities With Corticosteroidsmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, in the context of a clear danger signal, such as underlying inflammation, infection or trauma, all of which may constitute the danger signal, the risk of IDRs increases [52]. The usefulness of corticosteroids may be based on their ability to suppress the inflammatory response in the liver as a part of drug hypersensitivity or an immuno-allergic reaction, and this supports the speculation that an allergic mechanism may be involved in the TKIassociated liver injury seen in these patients [48,49]. Therefore, cautiously re-challenging after complete resolution of the liver injury under steroid administration and with very gradual dose increment may allow patients who have developed severe liver toxicity to continue taking the drug [51].…”
Section: Reversibility Of Toxicities With Corticosteroidsmentioning
confidence: 80%
“…Harbaum et al [41] and Ferrero et al [45] demonstrated that when corticosteroids are applied early after the onset of imatinib-induced hepatotoxicity, it may result in rapid and complete hepatic recovery. The concurrent use of corticosteroids with imatinib has also allowed the continuance of imatinib therapy without hepatotoxicity recurrence in many cases ( Table 2) [45][46][47][48][49][50][51].…”
Section: Reversibility Of Toxicities With Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of corticosteroids into the patient's regimen has been previously shown in a few case reports to enable use of imatinib in patients who develop recurrent hepatotoxicity, even at reduced doses 6 9 13 14. Steroids used in these case reports included oral prednisone 25 mg daily tapered over 5–8 months,6 prednisone 30 mg daily tapered over 5 months,9 prednisone 20 mg daily (duration not mentioned)13 and prednisone 25 mg twice daily (duration not mentioned) 14. The usefulness of corticosteroids may be based on their ability to suppress the inflammatory response in the liver as a part of drug-hypersensitivity or an immuno-allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that patients with an increased drug exposure had a better survival prognosis 23. In addition, rare but sometimes severe side effects have been reported with imatinib therapy 24–30. Taken together with the large interindividual pharmacokinetic variability,31 there is a rationale for monitoring plasma levels of imatinib and its metabolites, at least for research purposes.…”
Section: Introductionmentioning
confidence: 99%